APLIKASI KEGIATAN KKG UNTUK MENINGKATKAN KEMAMPUAN GURU AGAMA HINDU DALAM MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR - I Nyoman Matra (Pascasarjana Universitas Hindu Indonesia, 2015)
This research was designed to be a School Action Research planned to be conducted in two cycles; every cycle was conducted in two or three meetings. The subjects of the research were the Hinduism teachers of the elementary schools included in cluster 1 in Ubud district, Gianyar regency, consisting of 9 Hinduism teachers. Through the research conducted it can be concluded that from the cycle 1 and cycle 2, there has been an increase of the value mean obtained from each the observed as well as the assessed component. This means that the development and the guidance through the teacher working group discussion approach can improve the teacher competence in utilizing the school environment as the learning source.